2013
DOI: 10.1051/0004-6361/201220218
|View full text |Cite
|
Sign up to set email alerts
|

Discovering young stars in the Gum 31 region with infrared observations

Abstract: Context. The Gum 31 bubble, which contains the stellar cluster NGC 3324, is a poorly studied young region close to the Carina Nebula. Aims. We are aiming to characterise the young stellar and protostellar population in and around Gum 31 and to investigate the starformation process in this region. Methods. We identified candidate young stellar objects from Spitzer, WISE, and Herschel data. Combining these, we analysed the spectral energy distributions of the candidate young stellar objects. With density and tem… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
49
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(67 citation statements)
references
References 58 publications
8
49
0
Order By: Relevance
“…Cluster G286.38-0.26 Figure 7 shows the VISTA view of the cluster G286.38-0.26, which is partly embedded in a cloud clump in the southern edge of the dust bubble around Gum 31. The bluish and reddish stars trace the different populations of stars seen in front of the clump and embedded in the clump, as discussed in Ohlendorf et al (2013). A multiwavelength (optical to FIR) comparison of this cluster can be seen in Fig.…”
Section: Gum 31 H II Regionmentioning
confidence: 59%
See 1 more Smart Citation
“…Cluster G286.38-0.26 Figure 7 shows the VISTA view of the cluster G286.38-0.26, which is partly embedded in a cloud clump in the southern edge of the dust bubble around Gum 31. The bluish and reddish stars trace the different populations of stars seen in front of the clump and embedded in the clump, as discussed in Ohlendorf et al (2013). A multiwavelength (optical to FIR) comparison of this cluster can be seen in Fig.…”
Section: Gum 31 H II Regionmentioning
confidence: 59%
“…A multiwavelength (optical to FIR) comparison of this cluster can be seen in Fig. 12 of Ohlendorf et al (2013).…”
Section: Gum 31 H II Regionmentioning
confidence: 99%
“…The combination of the NIR data (J,H, and K s -band) of the VCNS with the Spitzer MIR data (3.6 μm, 4.5 μm, 5.8 μm, and 8.0 μm; Ohlendorf et al 2013) revealed new insight into the spatial distribution and the clustering properties of the young stellar populations in the CNC. The area covered simultaneously by both surveys is ∼5.30 deg 2 .…”
Section: Discussionmentioning
confidence: 99%
“…PAH emission from diffuse structures close to point sources can thus adulterate the photometric flux measurements in the IRAC bands 1, 3, (Bressan et al 2012) and the blue asterisks show the locus of the red supergiants, TP-AGBs, and upperRGBs produced with the dusty models. We also give the typical uncertainties of the photometry from Preibisch et al (2014) for the VISTA data and from Ohlendorf et al (2013) for the [4.5]-band. The color bar shows the number of objects per bin (bin size = 0.02 mag × 0.02 mag).…”
Section: The Spitzer Mir Catalogmentioning
confidence: 99%
“…Recent simulations of this process are shown by Hosokawa & Inutsuka (2005, 2006 and Dale et al (2007). An observational signature of this process is the presence of a dense layer and (more or less regularly spaced) massive condensations adjacent to the H ii region (e.g., Deharveng et al 2003Deharveng et al , 2005Zavagno et al 2006;Liu et al 2015;Pirogov et al 2013;Ohlendorf et al 2013). If the IF/SF encounters pre-existing denser region, it compresses them to induce star formation.…”
Section: Introductionmentioning
confidence: 99%